Chemical processes for the recovery of valuable metals from spent nickel metal hydride batteries: A review. (December 2022) - Cassayre, L.; Guzhov, B.; Zielinski, M.; Biscans, B.
Abstract: This work proposes a review of the various unit operations described in the literature for the specific recycling of nickel metal hydride batteries, with a large focus on the chemical reactions and processes. After a brief presentation of the characteristics of spent nickel metal hydride batteries and their composition, this review first describes the physical pretreatment methods, followed by the main principles and challenges of element separation by pyrometallurgy. Then, the main steps of hydrometallurgical processes (leaching, selective precipitation, solvent extraction, electrowinning) are analyzed, focusing on explaining the main difficulties and the most promising solutions. In addition, when available, recent thermodynamic models have been used to calculate equilibria for both pyrometallurgical and hydrometallurgical systems, with a view to provide elements of understanding in the choice of operating conditions for unit operations. Highlights: Spent nickel metal hydride batteries are secondary source of nickel and rare earths. Efficient element separation remains a challenge due to the battery complexity. Conventional pyrometallurgical routes and alternative thermal treatment are reviewed. Hydrometallurgical operations (leaching and separation methods) are reviewed. Recent thermodynamic models are powerful tools to better understand these processes.